The Local Food Environment and Obesity: Evidence from Three Cities - Walker, Blake Byron; Shashank, Aateka; Gasevic, Danijela; Schuurman, Nadine; Poirier, Paul; Teo, Koon; Rangarajan, Sumathy; Yusuf, Salim; Lear, Scott A. (Obesity (Silver Spring, Md.), 2020)
Objective This study aimed to identify the association between the food environment and obesity. Methods BMI and waist circumference (WC) were measured in 8,076 participants from three cities. The number of fast‐food restaurants, full‐service restaurants, bars/pubs, markets, and liquor stores within 500 m of each participant was documented. The association between the food environment (ratio of fast‐food to full‐service restaurants, ratio of bars/pubs to liquor stores, and presence of markets) with obesity (BMI ≥ 30 kg/m2) and abdominal obesity (WC ≥ 102 cm for males or WC ≥ 88 cm for females) was investigated, adjusted for age, sex, education level, neighborhood deprivation, neighborhood type, and total hours per week of walking and taking into account city‐level clustering. Results The ratios of fast‐food to full‐service restaurants and of bars/pubs to liquor stores were positively associated with obesity (OR = 1.05 [CI: 1.02‐1.09] and OR = 1.08 [CI: 1.04‐1.13], respectively). The ratio of bars/pubs to liquor stores was positively associated with abdominal obesity (OR = 1.10 [CI: 1.05‐1.14]). There was no association between markets and either obesity or abdominal obesity. Conclusions Features of the food environment have varying associations with obesity. These features have an additive effect, and future studies should not focus on only one feature in isolation.